THE PROBLEMS OF LANGUAGE TEACHING IN MODERN EDUCATION - Rahmatova, E’zoza (Innovative Development in Educational Activities, 2023)
This study attempted to examine the true problems in English education as well as the solutions implemented by English teachers. A number of concerns occurred, some of which were created by students, some by teachers, and some by the facilities at the school or college. Students struggle with a lack of linguistic understanding, poor concentration, a lack of discipline, a lack of interest, boredom, and difficulty speaking. Meanwhile, teachers confront challenges such as a lack of teacher training, a language competency issue, a limited understanding of teaching methods, unfamiliarity with technology, and a lack of professional development.